ChemInform Abstract: Hydrothermal Synthesis for New Multifunctional Materials: A Few Examples of Phosphates and Phosphonate‐Based Hybrid Materials. Issue 18 (April 2016) - Rueff, Jean‐Michel; Poienar, Maria; Guesdon, Anne; Martin, Christine; Maignan, Antoine; Jaffres, Paul‐Alain
Abstract: Review: 45 refs.